THE EFL STUDENTS’ PERCEPTION OF THEIR FOREIGN LANGUAGE ANXIETY IN SPEAKING CLASS - Dita Anggraeny; Iskhak Said; R. Bunga Febriani (Wahana Pendidikan, 2020)
ABSTRACTThe purpose of this paper is aimed at investigating the factors that influence foreign language anxiety among the students in a speaking class, and how they perceive about overcoming foreign language anxiety. The present study used a questionnaire to find out the factors that influenced students’ foreign language anxiety. An interview was conducted in order to find out the students’ perception of their foreign language anxiety. It was found that students felt anxious when they were unable to comprehend communication in class (62.5%). Test and speaking in front of class became one of the factors that caused students to experienced anxiety (43%). On the other hand, fear of receiving bad comments from the teacher and the other students was the third factor that students experienced anxiety (61.8%). Through the semi-structured interviews, it showed that students reduced the anxiety by practicing the pronunciation, and memorizing the vocabulary. Besides, the teacher played a role in creating and reducing students’ foreign language anxiety. The teacher who was able to create an enjoyable learning atmosphere, and focused on student-centered learning, the students argued that it could reduce their foreign language anxiety. Keywords: Speaking, Anxiety, Foreign Language Anxiety ABSTRAKTujuan dari artikel ini bertujuan untuk menyelidiki faktor-faktor yang mempengaruhi kecemasan bahasa asing di antara siswa di kelas berbicara, dan bagaimana mereka memandang tentang mengatasi kecemasan bahasa asing. Penelitian ini menggunakan kuesioner untuk mengetahui faktor-faktor yang mempengaruhi kecemasan bahasa asing siswa. Wawancara dilakukan untuk mengetahui persepsi siswa tentang kecemasan bahasa asing mereka. Ditemukan bahwa siswa merasa cemas ketika mereka tidak dapat memahami komunikasi di kelas (62,5%). Tes dan berbicara di depan kelas menjadi salah satu faktor yang menyebabkan siswa mengalami kecemasan (43%). Di sisi lain, ketakutan menerima komentar buruk dari guru dan siswa lain adalah faktor ketiga yang membuat siswa mengalami kecemasan (61,8%). Melalui wawancara semi-terstruktur menunjukkan bahwa siswa mengurangi kecemasan dengan mempraktikkan pengucapan, dan menghafal kosa kata. Selain itu, guru berperan dalam menciptakan dan mengurangi kecemasan bahasa asing siswa. Guru yang mampu menciptakan suasana belajar yang menyenangkan, dan fokus pada pembelajaran yang berpusat pada siswa, para siswa berpendapat bahwa itu dapat mengurangi kecemasan bahasa asing mereka. Kata kunci: Berbicara, Kecemasan, Kecemasan Bahasa Asing